Acerca de la importancia de la técnica del ‘iceberg’ o dato escondido como recurso narrativo - Huárag Álvarez, Eduardo (Pontificia Universidad Católica del Perú, 2024)
Following the definition of the “iceberg” theory, or theory of omission, we analyze its application in short stories and novels. The aim is to demonstrate its impact on the handling of suspense through its integration into the structure of fiction. As we shall see, the theory of omission influences the management of suspense, depending on the author’s creativity and the judicious withholding of information. In some cases, such information is entirely omitted. Thus, the iceberg theory is realized, an element that reveals only a fraction of its entirety, and by applying this principle, the primary event or incident remains elusive.

Luego de la definición de la técnica del “iceberg” o dato escondido, analizamos la utilización de este recurso en los relatos breves y en la novela. Se pretende demostrar el efecto que tiene en el manejo del suspenso el modo en que se le inserta en la estructura del relato. Ciertamente, como veremos, el dato escondido influye en el manejo del suspenso, dependiendo de la creatividad del autor y la dosificación de la información omitida. En algunos casos, tal información simplemente no figura. De ese modo se cumple la teoría del “iceberg”, elemento que deja ver solo una parte de su corporeidad y aplicando este principio diríamos que se elude el acontecimiento o incidente primordial.
On the importance of the iceberg technique or theory of omission as a narrative resource
Keywords: Technique; Fiction; Suspense; Suggestion; Art; Técnica; Narración; Suspenso; Sugerencia; Arte; https://purl.org/pe-repo/ocde/ford#6.00.00